Study of Entangled K-meson and Its Decoherence - Abas Syahbana; Freddy Permana Zen; Donny Dwiputra (Indonesian Journal of Physics, 2022)
In this paper, entangled K-meson model and decoherence phenomenon in thesystem is studied. Using Lindblad equation, dynamical equation of entangled K-meson systemthat interacts with the environment is obtained. We find that non-Hermitian Hamiltonian ofthe system makes completely positive and trace-preserving map (CPT-map) on the space ofdensity matrix does not satisfy trace preserving properties. We also find that purity of densitymatrix can be less than 1=d which does not satisfy the property of purity. From the dynamicalequation, parameters related to the decoherence of the system, decoherence parameter (λ) andeffective decoherence parameter (ζ), are determined. Using Standard Least-Squares method,we obtain ζ = 0; 13±0; 865. This result is in accordance with references result that use effectivevariance method, ζ = 0; 13±+0 -0;;16 15. We show that ζ = 0; 13±+0 -0;;16 15 corresponds with referencesresult, λ = (1; 84±+2 -2;;50 17) × 10-12 MeV. The value of both parameters are close to zero relativeto ζ = 1 or λ ! 1. It means that the interaction between system and environment doesnot affect the system significantly. Therefore, quantum properties in the system related to theentanglement of the strangeness is preserved.